(untitled) (ENTHYMEMA, 2010)
What is Tradition? We usually (and wrongly) think it coincides with History. It would be better to think of Traditions, that is various experiences that co-exist in history and can be picked up to build on one’s system of values to be passed on to future generations. Our knowledge is actually based on traditions, and literature makes no exception. In this paper the author shows how one tradition, i.e. the comic-humoristic one, has marked European culture and literature. Its extraordinary genealogy has been written down by Gerard de Nerval: from Apuleius through Petronius, Swift, Diderot, Voltaire, up to Lawrence Sterne. Nevertheless, in the course of time, the comic-humoristic tradition has been able to attract many other novelists, poets and artists who have brilliantly enriched our cultural experience. It is possible to go back to the nineteenth century and track down many lines of the comic-humoristic tradition acting in European cultures, in order to show their dynamics, their interactions and their influence even at the outset of children’s literature.